Kali kerberti - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Kali kerberti (Weber, 1913). To 27 cm (10.6 in) TL (Smith in Carpenter and De Angelis 2016). Circumglobal; Oregon (Personal communication: University of Washington, Burke Museum of Natural History and Culture Fish Collection, Seattle, Washington). Bathypelagic; depth: 200–4,465 m (656–14,645 ft) (Melo 2008). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 192, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008